The Oral Complications of COVID-19 - Zhou, Xinxuan; Dong, Jiajia; Guo, Qiang; Li, Mingyun; Li, Yan; Cheng, Lei; Ren, Biao (Frontiers in Molecular Biosciences, 2022)
Background: COVID-19 is a novel coronavirus infectious disease associated with the severe acute respiratory syndrome. More and more patients are being cured due to the development of clinical guidance for COVID-19 pneumonia diagnosis, treatment, and the vaccines. However, the long-term impact of COVID-19 on patients after recovery is unclear. Currently available reports have shown that patients recovered from COVID-19 continue to experience health problems in respiratory and other organ systems. Oral problem is one of the important complications which has serious impacts on the rehabilitation and future quality of life, such as ageusia and macroglossia, but the oral complication is often being neglected. Aim of Review: From the perspective of stomatology, we summarized and elaborated in detail the types, pathogenesis of oral complications from COVID-19 patients after rehabilitation, and the reported prevention or treatment recommendations which may improve the COVID-19 patients' associated oral diseases. Key Scientific Concepts of Review: (1) To understand the common oral complications and the mechanisms of the development of oral complications after the COVID-19 recovery; (2) To summary the practical strategies to prevent the oral complications and construct the rehabilitation plans for patients with oral complications.